Implementasi Manajemen Perubahan Terhadap Kinerja Pendidik Dan Tenaga Kependidikan Di Mts Negeri 3 Medan - Kristanti Widayani (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This study aims to determine the role of the principal, how to plan, organize, monitor, evaluate and implement change management. Then to see the performance of educators and education personnel after the change, as well as the supporting and inhibiting factors in making change management. In this study using qualitative research methods with qualitative descriptive. This research was conducted at MTs Negeri 3 Medan. The technique used in collecting data is data collection techniques, namely interview, observation and documentation techniques. This study has 4 findings, namely: (1) The role of the principal in improving the performance of teachers and education personnel (2) The process of planning, organizing, monitoring, evaluating and implementing change management. (3) The performance of educators and education personnel after the changes are made. (4) factors supporting and inhibiting change management.